Exploring the nanofiltration mass transfer characteristic and concentrate process of procyanidins from grape juice. Issue 5 (26th April 2019) - Li, Cunyu; Ma, Yun; Li, Hongyang; Peng, Guoping
Abstract: In order to separate procyanidins from grape juice at room temperature, a separation prediction model was established based on nanofiltration. The mass transfer coefficient was positively correlated with the initial concentration. Nanofiltration performance of procyanidins was affected by filtration conditions, membrane properties, and molecular states. The correlation between mass transfer coefficient and initial concentration was established based on the linear equations of the rejection and mass transfer coefficient. The rejection of procyanidins predicted with the mass transfer model was in accordance with the experimental value, and the antioxidant activity was preserved effectively. The mathematical model could predict the rejection of procyanidins. The nanofiltration technology for procyanidin separation from grape juice was characterized by fast separation, low energy consumption, and zero oxidization loss. The nanofiltration technology could greatly improve the utilization efficiency of food products and decrease the energy consumption. Abstract : The nanofiltration technology for procyanidin separation from grape juice was characterized by fast separation, low energy consumption, and zero oxidization loss.